Aplikasi Pengenalan Anatomi Manusia Berbasis Augmented Reality - Akbar Triyudha Sakti; Hajar Sejati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Augmented Reality (AR) is an attempt to combine the real world and the virtual world in real-time. A real object that serves as a marker is used for positioning virtual objects that have been identified by the camera. Augmented Reality is widely used in various fields, one of which is the field of education. In the field of education Augmented Reality is used as an interactive learning media to be more creative, interesting and innovative. This Augmented Reality technology can be applied in the human anatomy learning system. The use of Augmented Reality technology is expected to display objects in the form of 3D virtual human body parts in a marker book as props. Markers detected by an android-based smartphone camera will display anatomical objects that will be used by the teacher, so that students can observe how the human anatomy looks in realtime.